2014
DOI: 10.1186/1755-8794-7-49
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome-wide analysis of CIK cells identify distinct roles of IL-2 and IL-15 in acquisition of cytotoxic capacity against tumor

Abstract: BackgroundCytokine-induced killer (CIK) cells are an emerging approach of cancer treatment. Our previous study have shown that CIK cells stimulated with combination of IL-2 and IL-15 displayed improved proliferation capacity and tumor cytotoxicity. However, the mechanisms of CIK cell proliferation and acquisition of cytolytic function against tumor induced by IL-2 and IL-15 have not been well elucidated yet.MethodsCIKIL-2 and CIKIL-15 were generated from peripheral blood mononuclear cells primed with IFN-γ, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Degree centrality is defined as the link numbers one node has to the other. 29 Co-expression network analysis showed that FABP5P3, LOC100996732, LOC100996735, ZFAS1 and ZEB1-AS1 are central lncRNAs (Supplementary Table S2). We then tested the role of these five lncRNAs in cell growth.…”
Section: Lncrnas Expression Profile In Hccmentioning
confidence: 99%
“…Degree centrality is defined as the link numbers one node has to the other. 29 Co-expression network analysis showed that FABP5P3, LOC100996732, LOC100996735, ZFAS1 and ZEB1-AS1 are central lncRNAs (Supplementary Table S2). We then tested the role of these five lncRNAs in cell growth.…”
Section: Lncrnas Expression Profile In Hccmentioning
confidence: 99%
“…IL-15 mainly promotes proliferation and differentiation of CD8+ T cells (56) and NK cells and serves as a homing factor in recruiting target immune cells to sites of production (57) . In comparison to IL-2, IL-15 appears to promote a more durable CD8+ memory T cell phenotype, induce more enhanced cell proliferation (58) and increase cell survival by upregulation of anti-apoptotic genes such as bcl-2 or downregulation of proapoptotic genes such as BIM and NOXA, even protecting them from IL-2 induced AICD (59, 60) .…”
Section: Interleukin-15mentioning
confidence: 99%
“…Within the network analysis, degree centrality is the most simplest and important measures of the centrality of a gene within a network that determines the relative importance. Degree centrality is defined as the link numbers one node has to the other (24). Coexpression network analysis showed that FABP5P3, LOC100996735, LOC100996732, ZEB1-AS1, and ZFAS1 are core lncRNAs.…”
Section: Lncrnas Expression Profile In Hccmentioning
confidence: 99%